A Model for Providing Free Patient Care and Integrating Student Learning and Professional Development in an Interprofessional Student‐Led Clinic. Issue 2 (2017) - George, Lydia; Bemenderfer, Sara; Cappel, Maggie; Goncalves, Kathryn; Hornstein, Micaela; Savage, Chelsea; Altenburger, Peter; Bellew, James; Loghmani, Terry M.
Abstract : Background and Purpose. : The need to reduce the barriers of access and affordability in health care is evident. The Indiana University Student Outreach Clinic (IU SOC) is a community‐based, pro bono, interprofessional, student‐led clinic dedicated to removing barriers to health care. The purpose of this report is to describe the implementation approach, sustainability efforts, and initial outcomes of this community‐based physical therapy clinic model with the aim of making it transparent for others to replicate. Method/Model Description and Evaluation. : An overview of the IU SOC, implementation and sustainability of the physical therapy clinic model, and student learning opportunities are described. Keys to successful implementation are enumerated. Learning opportunities include: clinical competency, professional values, civic engagement, interprofessional education and collaborative practice (IPECP), peer mentorship, and leadership development. Outcomes. : Preliminary clinic and learning opportunity outcomes collected from patient databases and student surveys and reflections suggest the IU SOC is having a positive impact on the community it serves by providing care patients would otherwise have not received, while simultaneously supporting learning. Patient volume and student participation are expanding. Initial outcomes suggest this model is valuable for the professional growth of future physical therapists. Discussion and Conclusion : The impact of this clinic model on the community and students is just beginning to be realized and understood. Key elements of success are that it's (a) community‐based, (b) interprofessional, and (c) highly collaborative. Free, student‐led, interprofessional health care clinics may offer an important means for improving health care access while simultaneously preparing entrylevel professionals for practice.